2013
DOI: 10.1364/oe.21.009573
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared supercontinuum generation in a suspended-core As_2S_3 chalcogenide microstructured optical fiber

Abstract: We demonstrate the supercontinuum (SC) generation in a suspended-core As(2)S(3) chalcogenide microstructured optical fiber (MOF). The variation of SC is investigated by changing the fiber length, pump peak power and pump wavelength. In the case of long fibers (20 and 40 cm), the SC ranges are discontinuous and stop at the wavelengths shorter than 3500 nm, due to the absorption of fiber. In the case of short fibers (1.3 and 2.4 cm), the SC ranges are continuous and can extend to the wavelengths longer than 4 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(57 citation statements)
references
References 42 publications
1
54
0
2
Order By: Relevance
“…In recent years, several experimental and theoretical investigations on mid-infrared SC generation were reported in ChG planar waveguides [13][14][15], ChG fibers [16][17][18][19][20][21][22][23][24][25][26][27][28], single crystal sapphire fibers [29], silicon-on-insulator (SOI) wire waveguides [30], ZBLAN fiber [31], fluoride glass [32] and germano-silicate fibers [33]. Gai et al [13] reported SC generation from 2.9 µm to 4.2 µm in dispersion-engineered As 2 S 3 glass rib waveguide (6.6 cm long) pumped with 7.5 ps duration pulses at a wavelength of 3.26 µm with a pulse peak power of around 2 kW.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several experimental and theoretical investigations on mid-infrared SC generation were reported in ChG planar waveguides [13][14][15], ChG fibers [16][17][18][19][20][21][22][23][24][25][26][27][28], single crystal sapphire fibers [29], silicon-on-insulator (SOI) wire waveguides [30], ZBLAN fiber [31], fluoride glass [32] and germano-silicate fibers [33]. Gai et al [13] reported SC generation from 2.9 µm to 4.2 µm in dispersion-engineered As 2 S 3 glass rib waveguide (6.6 cm long) pumped with 7.5 ps duration pulses at a wavelength of 3.26 µm with a pulse peak power of around 2 kW.…”
Section: Introductionmentioning
confidence: 99%
“…A fabricação relativamente fácil de fibra óptica a partir de vidros calcogenetos permite o confinamento da luz necessário para que a soma dos diferentes efeitos não lineares resultem num supercontínuo de luz. [94][95][96] Recentemente, a geração de um supercontínuo de luz cobrindo a faixa 1,4 -13,3 µm foi obtida numa fibra de calcogeneto. 97 A alta não linearidade dos vidros calcogenetos, como o deslocamento Raman, também pode ser usado para a emissão de luz no infravermelho.…”
Section: Emissão Da Luz No Infravermelhounclassified
“…Assim foi obtido um efeito laser em 3,77 μm em uma fibra calcogeneto através da combinação da não linearidade do material de calcogeneto e a emissão em 3,0 μm obtida numa fibra de fluoreto dopada com érbio Er 3+ . 93,94 A dopagem de vidros calcogenetos com íons de terras raras no intuito de obter emissão no infravermelho também é um domínio muito explorado por vários grupos de pesquisa. [98][99][100] Devido ao seu alto índice de refração e sua baixa energia de fônon, altas seções eficazes de absorção (absorption cross-section) e emissão, assim como baixas relaxações multifonon (e, consequentemente, alto rendimento quântico de luminescência) são esperadas nos vidros calcogenetos.…”
Section: Emissão Da Luz No Infravermelhounclassified
“…Dispersion of the waveguide plays an important role in determining the supercontinuum spectrum. Ideally dispersion near the pump wavelength should be small in magnitude as well as relatively flat in nature [26]. Chalcogenide glasses generally have smaller material dispersion than silicon.…”
Section: Theorymentioning
confidence: 99%